VARIATION IN ABSORPTION OF PHOTOSYNTHETIC ACTIVE RADIATION (PAR) AND PAR USE EFFICIENCY OF WHEAT AND MUSTARD GROWN UNDER INTERCROPPING SYSTEM - S. JENA; S. BASU; S. MAJI; P. BANDOPADHYAY; R. NATH; PRAMITI K. CHAKRABORTY; P. K. CHAKRABORTY (The Bioscan, 2014)
Absorption of PAR (Photosynthetic active radiation) by wheat and mustard crop and PAR use efficiency were estimated from a two year experiment of wheat-mustard intercropping system. The experiment comprised of five treatments (T1-sole wheat, T2- sole mustard, T3 -two wheat: six mustard, T4: four wheat: four mustard, T5: six wheat: two mustard) allotted to RBD with 6 replications in a plot of 54m2. The sole wheat absorbed nearly 80% of the incident PAR at 11.30h throughout growth phases. Among the intercrop treatments, T4 recorded very high absorption. In mustard, T3 absorbed approximately 80% of the incident PAR. Mean RUE (Radiation use effi- ciency) for dry matter production in wheat ranged from 1.84-2.99 g MJ-1 for different treatment combinations and in mustard, it ranged from 2.33-4.34 g MJ-1. The RUE for grain yield ranged from 1.07 to 2.88 g MJ-1 and 0.43 to 1.23g MJ-1 for wheat and mustard respectively. Sole crop recorded higher RUE than the component crops under intercropping.